Benzo-Extended Cyclohepta[def]fluorene Derivatives with Very Low-Lying Triplet States - Wu, Fupeng; Ma, Ji; Lombardi, Federico; Fu, Yubin; Liu, Fupin; Huang, Zhijie; Liu, Renxiang; Komber, Hartmut; Alexandropoulos, Dimitris I.; Dmitrieva, Evgenia; Lohr, Thorsten G.; Israel, Noel; et al. (Angewandte Chemie International Edition, 2022)
Open-shell non-alternant polycyclic hydrocarbons (PHs) are attracting increasing attention due to their promising applications in organic spintronics and quantum computing. Herein we report the synthesis of three cyclohepta[def]fluorene-based diradicaloids (1–3), by fusion of benzo rings on its periphery for the thermodynamic stabilization, as evidenced by multiple characterization techniques. Remarkably, all of them display a very narrow optical energy gap (Egopt=0.52–0.69 eV) and persistent stability under ambient conditions (t1/2=11.7–33.3 h). More importantly, this new type of diradicaloids possess a low-lying triplet state with an extremely small singlet–triplet energy gap, as low as 0.002 kcal mol−1, with a clear dependence on the molecular size. This family of compounds thus offers a new route to create non-alternant open-shell PHs with high-spin ground states, and opens up novel possibilities and insights into understanding the structure–property relationships.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Azulenes; Fused-Ring Systems; Magnetic Properties; Open-Shell Diradicaloids; Polycyclic Hydrocarbons